Current concept in alveolar cleft management - Khan, Mohammad Sayedur Rahman; Shuang, Mei; Liu, Xiao Lin; Xu, Sun; Liang, Hao Fu (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
The alveolar cleft is known as the developmental defect of bone in alveolar process of maxillae which occurs in 75% of the cleft lip and palate patients with different types of clinical presentation like unilateral or bilateral and complete or incomplete. Secondary alveolar cleft reconstruction with autogenic spongy bone grafting (osteoplasty) at the stage of mixed dentition is commonly accepted treatment to help in the maintenance of maxillary arch continuity, repairing of oronasal fistula, eruption of the permanent dentition, enhancement of nasal symmetry through providing alar base support and improving speech. As of late, conflicting argument of alveolar cleft management is continuing regarding treatment planning with timing, graft materials, surgical techniques as well as methods of evaluation of the progress of alveolar osteoplasty. Now-a-days, experiments have made for the application of allogeneic bone, artificial bone, and recombinant human bone morphogenetic protein (rhBMP), along with growth factors to diminish the donor-site morbidity associated autogenic bone grafting. The purpose of this review is to discuss about pathogenesis and aetiology of cleft defects, surgical techniques, assessment of progress of alveolar bone graft and proposed future materials for bone graft.